Korean Restaurants’ Consumer Needs Based on Marketing Mix Through the Kano Model - Caesarilla Maggie Zavira; Dyah Ismoyowati; Henry Yuliando (Universitas Muhammadiyah Yogyakarta, 2023)
A proliferation of Korean restaurants in Yogyakarta can be seen over the past few years, each with its unique concept. However, a survey on Google Star Rating suggests that not all of these restaurants are sustainable. The significant discrepancy between expectations and actual satisfaction of consumers is likely a contributing factor. Moreover, intense competition exists between these restaurants. This study aims to identify which aspects of marketing—such as product, price, place, promotion, people, process, and physical evidence—influence Korean restaurants’ consumer needs. Using the Kano model, consumer satisfaction was analyzed by classifying consumer needs into attractive, must-be, one-dimensional, indifferent, reverse, or questionable categories. Purposive and snowball sampling methods were employed to select 100 respondents to complete a questionnaire. The results unveiled that four of the seven marketing mix attributes needed by Korean restaurants’ consumers fell into the one-dimensional category. The features consisted of physical evidence (clean dining room), people (clean and tidy employee appearance), product (good taste), and process (timely service). Furthermore, the attributes of unique offers (D1); fast service (F2); menu information, ingredients, how to cook it (E3); and affordable food prices (B1) contributed to greater consumer satisfaction. These attributes boosted consumer satisfaction by 80%, 79.8%, 74.5%, and 73.7%, respectively.